Punching shear strength of continuous post-tensioned concrete flat plate. - Kallage, Mahmoud Rezai. (University of Ottawa (Canada), 1993)
A two bay by two bay continuous, unbonded post-tensioned flat plate was constructed and loaded to failure. The slab was designed in accordance with the provisions of ACI 319-89 except that no supplementary bonded reinforcing steel was provided. The prestressing tendons were uniformly distributed in one direction and banded in span/6 column strips in the other direction. In both directions the average prestress on the concrete was 3.5 MPa. The dimensions of each bay were 2.75 m, the slab thickness was 89 mm, mean concrete cylinder strength was 44 MPa. The load was applied monotonically until punching shear occurred at an edge column on the side parallel to banded tendons. The failed column was shored and the slab reloaded until punching shear occurred at the interior column. The lack of supplementary bonded reinforcing steel in regions of moment transfer had no apparent detrimental effects so it must be concluded that the prestress was effective right to the edge of the concrete. The use of 100% banded tendons in one direction and uniform distribution in the other direction had no adverse effects on either the flexural or punching shear behaviour. The literature was reviewed to locate experimental results of punching shear tests for isolated prestressed concrete flat plates, continuous prestressed flat plate systems and tests of flat plate column connections under shear and moment transfer. The strength capacities calculated using the provisions of ACI 318-89, CSA A23.3-84M, BS8110-85 and the CEB Model Code 1990 were compared to the test results and those from the literature review.
Keywords: Engineering, Civil.